A critical interpretive synthesis of the intersection of domestic violence with parental issues of mental health and substance misuse. (23rd March 2020) - Isobe, Jasmin; Healey, Lucy; Humphreys, Cathy
Abstract: A critical interpretive synthesis (CIS) methodology was used with the aim of informing practice with children and families when domestic and family violence (DFV) and parental issues relating to alcohol and other drugs (AOD) and mental health (MH) are also present. A CIS is grounded in the literature, but includes questioning of the literature in order to problematise gaps, contradictions and constructions of issues. A review of the literature from 2010 to 2018 was conducted with the structured search strategy identifying 40 relevant research articles. Synthesis and critique of these articles revealed three mutually informative themes through which to understand the literature and how it can inform practice. They were as follows: differences in theoretical approaches and client focus; complexity of system's collaboration; and practices converging on mothers. Taken together, these themes facilitated the development of the synthesising construct: strengthening intersection between DFV, AOD and MH sectors . Attention to practice at multiple levels that responds to the dynamics of gender and the differing impacts of violence was often lacking, particularly in the context of heightened child protection concerns where collaboration between sectors is needed. Both promising and problematic practices relating to gender dynamics and accountability converged on mothers. While there were exceptions, generally, there was an absence of engagement with, and recognition of, the impacts of fathers' patterns of using violence and control on adult and child survivors. Promising practice related to the strengthening of the mother–child relationship and attention to MH and its intersection with domestic violence. Strengthening the intersections between DFV, AOD and MH practices with attention to keeping the perpetrator of violence in view is critical to overcoming the poor practice that can occur when sectors are siloed from each other.